13C-NMR dereplication of Garcinia extracts: Predicted chemical shifts as reliable databases - Bruguière, Antoine; Derbré, Séverine; Coste, Chloé; Le Bot, Maxime; Siegler, Benjamin; Leong, Sow Tein; Sulaiman, Syazreen Nadia; Awang, Khalijah; Richomme, Pascal (Elsevier, 2018)
Usually isolated from Garcinia (Clusiaceae) or Hypericum (Hypericaceae) species, some Polycyclic Polyprenylated AcylPhloroglucinols (PPAPs) have been recently reported as potential research tools for immunotherapy. Aiming at exploring the chemodiversity of PPAPs amongst Garcinia genus, a dereplication process suitable for such natural compounds has been developed. Although less sensitive than mass spectrometry, NMR spectroscopy is perfectly reproducible and allows stereoisomers distinction, justifying the development of 13C-NMR strategies. Dereplication requires the use of databases (DBs). To define if predicted DBs were accurate enough as dereplication tools, experimental and predicted δC of natural products usually isolated from Clusiaceae were compared. The ACD/Labs commercial software allowed to predict 73% of δC in a 1.25 ppm range around the experimental values. Consequently, with these parameters, the major PPAPs from a Garcinia bancana extract were successfully identified using a predicted DB.